A Brief, Critical Review of Research on Impaired Control Over Alcohol Use and Suggestions for Future Studies. (7th October 2013) - Leeman, Robert F.; Beseler, Cheryl L.; Helms, Christa M.; Patock‐Peckham, Julie A.; Wakeling, Vanessa A.; Kahler, Christopher W.
<x xml:space="preserve">Abstract</x> Impaired control, defined as "a breakdown of an intention to limit consumption" (Heather et al. J Stud Alcohol 1993; 54, 701), has historically been considered an important aspect of addiction. Despite recognition of its importance to addiction and potential value as an early indicator of problem drinking risk, we argue that impaired control over alcohol use has not received sufficient research attention. In an effort to spark further research, the present critical review offers brief discussion of the current state of knowledge regarding impaired control and avenues for future research. Three main research areas are addressed: (i) epidemiology; (ii) measurement issues; and (iii) potential mechanisms underlying relationships between impaired control and subsequent problem drinking. Measurement issues include complexities involved in self‐report assessment of impaired control, development and validation of human and animal laboratory models, and impaired control's relationship to other constructs (i.e., impulsivity and other difficulties with self‐control; symptoms of dependence such as craving). We discuss briefly 2 potential mechanisms that may help to explain why some drinkers experience impaired control while others do not: neurobiological dysfunction and family history/genetics. Suggestions for future research are focused on ways in which the impaired control construct may enhance prediction of who might be at particular risk of subsequent problem drinking and to facilitate intervention to reduce problem alcohol use.